”Hvorfor så meget stabilitet”? Stabiliserende elementer i det danske politiske system - Munkøe, Malthe (Politik, 2012)
Social choice research has shown that collective preference aggregation mechanisms under some conditions will produce arbitrary results, and are prone to endless cycles or strategic manipulation. is prompted Tul- lock (1981) to ask the question “Why so much stability”? at is to say, what explains the discrepancy between these results which implicates that politics is chaotic and random, and general understanding of how politics works in practice. e literature has identi ed a number of mechanisms, including “structure-inducing” in- stitutions that have a stabilizing e ect on the political system. As such it is ultimately an empirical question to what extent a political system is stable or not, and what institutions, norms and arrangements engender stability. is article considers the Danish political system from the point of view of social choice theory and discusses which institutions and arrangements work to stabilize it.